Desarrollo de un prototipo de aprovechamiento de aguas lluvias y afluentes hídricas a través de un sistema mecánico de bombeo, para cubrir las necesidades básicas insatisfechas en viviendas rurales del municipio de Ibagué. - Moreno Córdoba, Héctor Hugo
Dignifying housing in rural areas requires the inclusion of sustainable systems and the incorporation of essential services. The water resource depends to a great extent on the nearby tributaries, the use of rainwater and the administration of said resource by the communities. The purpose of this project is to develop a prototype for the use of rainwater and water tributaries through a mechanical pumping system, to cover the unsatisfied basic needs in rural homes. Two systems are identified: a) rainwater harvesting, b) ram-type mechanical pumping. These two systems complement each other for the conduction of water to rural homes, the collection of rainwater and the collection of water from water sources. Finally, this project may be used as a water supply mechanism for rural homes that do not have this essential service, for any region of the Colombian territory.